A Baseline Measure of Tree and Gastropod Biodiversity in Replanted and Natural Mangrove Stands in Malaysia: Langkawi Island and Sungai Merbok - Brenda Hookham; Aileen Tan Shau-Hwai; Benoit Dayrat; William Hintz (Tropical Life Sciences Research, 2014)
The diversities of mangrove trees and of their associated gastropods were assessed for two mangrove regions on the west coast of Peninsular Malaysia: Langkawi Island and Sungai Merbok. The mangrove area sampled on Langkawi Island was recently logged and replanted, whereas the area sampled in Sungai Merbok was part of a protected nature reserve. Mangrove and gastropod diversity were assessed in four 50 m2 (10 × 5 m) sites per region. The species richness (S), Shannon Index (H’) and Evenness Index (J’) were calculated for each site, and the mean S, H’ and J’ values were calculated for each region. We report low tree and gastropod S, H’ and J’ values in all sites from both regions. For Langkawi Island, the mean S, H’ and J’ values for mangrove trees were S = 2.00±0, H’ = 0.44±0.17 and J’ = 0.44±0.17; the mean S, H’ and J’ values for gastropods were S = 4.00±1.63, H’ = 0.96±0.41 and J’ = 0.49±0.06. In Sungai Merbok, the mean S, H’ and J’ values for mangrove trees were S = 1.33±0.58, H’ = 0.22±0.39 and J’ = 0.22±0.39; the mean S, H’ and J’ values for gastropods were S = 4.75±2.22, H’ = 1.23±0.63 and J’ = 0.55±0.12. This study emphasises the need for baseline biodiversity measures to be established in mangrove ecosystems to track the impacts of anthropogenic disturbances and to inform management and restoration efforts. Kepelbagaian pokok bakau dan gastropod yang berkaitan telah dikaji di dua kawasan bakau di pantai barat Semenanjung Malaysia: Pulau Langkawi dan Sungai Merbok. Kawasan bakau yang disampel di Pulau Langkawi baru dibalak dan ditanam semula, manakala kawasan yang disampel di Sungai Merbok adalah sebahagian daripada rizab semula jadi yang dilindungi. Kepelbagaian bakau dan gastropod dinilai dalam empat tapak kajian bersaiz 50 m2 (10 × 5 m) bagi setiap kawasan. Nilai kekayaan spesies (S), Indeks Shannon (H’) dan indeks evenness (J’) dikira bagi setiap tapak kajian, dan nilai min S, H’ dan J’ dikira bagi setiap kawasan. Keputusan menunjukkan nilai S, H’ dan J’ bagi pokok dan gastropod dari kesemua kawasan kajian dari kedua-dua tapak adalah rendah. Untuk Pulau Langkawi, nilai min S, H’ dan J’ bagi pokok bakau adalah S = 2.00±0, H = 0.44±0.17 dan J’ = 0.44±0.17; nilai min bagi gastropod adalah S = 4.00±1.63, H’ = 0.96±0.41 dan J’ = 0.49±0.06. Di Sungai Merbok, nilai min S, H’ dan J’ bagi pokok bakau adalah S = 1.33±0.58, H’ = 0.22±0.39 dan J’ = 0.22±0.39; nilai min bagi gastropod adalah S = 4.75±2.22, H’ = 1.23±0.63 dan J’ = 0.55±0.12. Kajian ini menekankan keperluan ukuran kajian asas biodiversiti diadakan untuk ekosistem bakau untuk mengesan impak gangguan antropogenik dan sebagai panduan untuk usaha-usaha pengurusan dan pemulihan ekosistem bakau.